(untitled) (Research, Society and Development, 2022)
Racial differences are associated with social inequalities and condition people’s way of life, and can determine the health and illness of a given group. The purpose of this research was to analyze mortality by underlying cause of death, survivorship and differentials by race/color and sex in Bahia. This is an epidemiological, quantitative study, with secondary data from the SIM. The association between the variables “basic cause of death” and “race/color” was evaluated using the chi-square test, the relationships between all categories of both variables were studied in a simple correspondence analysis, and if a survival analysis to compare the curves. The results reveal that women have a better survival time than men. There is a statistically significant association between cause of death and race/color (p<0.0001). The data suggest that there are specific causes of death according to race/color. We found no statistically significant differences in the mean survival of whites when compared to yellows. Browns die mainly from external causes and have the shortest average survival time, approximately 10 years less than whites. Blacks die mainly from infectious and parasitic diseases, and have an average of 7.9 years of survival less than whites. Indigenous people die mainly from mental and behavioral disorders and have 8.5 years less survival. Conclusion: Women have a higher mean survival than men. Although the overall average survival has shown an upward trend, in the race/color categories there are differences in the average, differences that are maintained over the years.